Macroprolactin does not contribute to elevated levels of prolactin in patients on renal replacement therapy - YAVUZ, DİLEK; ŞİRİKÇİ, ÖNDER (WILEY, 2005)
Objective Three molecular forms of PRL with molecular weights of 23, 50-60 and > 100 kDa have been defined. The high-molecular-weight forms are called macroprolactin. Different immunoassays produce varyingly elevated results with macroprolactin-containing sera. The kidneys are reported to clear 25% of PRL from the circulation. Hyperprolactinaemia is seen in 20-75% of patients with chronic renal failure (CRF). PRL clearance rate has been reported to be reduced in CRF and the resulting hyperprolactinaemia is due to reduced renal function. Patients To determine the contribution of macroprolactinaemia to elevated PRL levels in CRF, 91 patients receiving haemodialysis (HD), continuous ambulatory peritoneal dialysis (CAPD) and renal transplantation (RT) therapies and 72 control subjects were included in the study. Measurements Serum PRL levels were measured by a sandwich immunoassay with electrochemical detection. Following polyethylene glycol (PEG) precipitation, recovery ratios were calculated and samples with a recovery of < 50% were identified as having macroprolactin isoforms. Results The serum and supernatant PRL levels of CRF patients were significantly higher than those of the control group (P < 0.001). The serum PRL levels of HD and CAPD patients were significantly higher than those of the RT patients (P < 0.001). The serum PRL levels of the RT patients and the control group did not differ significantly (P > 0.05). A moderate correlation was found between PRL and creatinine levels (r = 0.609, P < 0.001). Conclusions The hyperprolactinaemia seen in renal replacement therapy is not associated with the presence of macroprolactin isoforms but with the decline in renal function.
Keywords: POLYETHYLENE-GLYCOL PRECIPITATION; HYPERPROLACTINEMIA; HORMONES; EXPERIENCE; CLEARANCE; FAILURE; BIG